Education of Internet Marketing for Traditional Craftsmen of Baduy - Suharyati Suharyati; Ika Nurlaili Isnainiyah (Institute for Research and Community Services, 2019)
Regulation of the Minister of Home Affairs of the Republic of Indonesia No.1 of 2013 explain that the Indonesian government continues to strive to alleviate poverty and improve the welfare of the population through community empowerment activities. The 4.0 industrial revolution era triggered the digital technology trend, especially the internet to support product marketing, e.g. by reducing marketing costs and labor costs. However, the lack of technological knowledge is undeniable on a number of Indonesian population, such as MSME entrepreneurs of Outer Baduy traditional craftsmen in the Kanekes village. Government support is needed through ongoing activities with higher education institutions to provide education and assistance on product marketing (internet marketing). Community service held by lecturers from the Faculty of Economics, UPN Veteran Jakarta, aims to empower and raise the knowledge of the Outer Baduy community regarding internet marketing education and practice using social media. The approach used in this activity consists of talks, module creation, tutorials and practice on product marketing strategies using social media such as Instagram and Facebook. Based on the questionnaire analysis results, it is identified that the understanding of social media features for the promotion, networking and marketing expansion from participants has reached 68,57%. Keywords: internet marketing; social media; Instagram; Baduy